Alien worlds : how insects conquered the Earth, and why their fate will determine our future - Nicholls, Steve (Princeton University Press, 2023)
"Life on Earth depends on the busy activities of insects, but global populations of these teeming creatures are currently under threat, with grave consequences for us all. Alien Worlds presents insects and other arthropods as you have never seen them before, explaining how they conquered the planet and why there are so many of them, and shedding light on the evolutionary marvels that enabled them to thrive. Blending glorious imagery with entertaining and informative science writing, this book takes you inside the hidden realm of insects and reveals why their fate carries profound implications for our own."--Dust jacket flap.